Cardiometabolic risk and gut microbial phytoestrogen metabolite phenotypes. Issue 1 (30th August 2016) - Frankenfeld, Cara L.
Abstract : Dietary phytoestrogens are found in plants and have several biological activities that may be relevant to human health, including activities that are associated with cardiometabolic risk factors. These compounds are metabolized by gut bacteria to other compounds, which then have their own biological activities. This paper reviews the evidence regarding the role of phytoestrogen metabolism for cardiometabolic risk factors. Abstract : Recent evidence supports that the gut microbial community, independently and/or interactively with dietary intake, is a target for reducing cardiovascular disease risk through its effects on cardiometabolic risk factors. Dietary phytoestrogens may be a source for interactive effects. Phytoestrogens, such as isoflavones, lignans, and flavonoids, are compounds found in plants that have estrogenic or antiestrogenic activities, as well as antioxidant, antiproliferative, or apoptotic actions. Given these physiological activities, phytoestrogens may have a role in cardiometabolic health. Some phytoestrogens consumed in the diet undergo biotransformation through gut bacterial metabolism to other compounds that may exhibit similar or different physiological activity than the parent compound. There is interindividual variability in the capability to metabolize phytoestrogens to their metabolites, and there is a resulting phenotype that can be evaluated based on urinary metabolite excretion. Evidence suggests that phytoestrogen metabolites and/or phenotypes are associated with cardiometabolic risk factors, such as blood pressure, abdominal obesity, and serum lipids, triglycerides, glucose, and inflammatory markers. The objective of this review was to provide an overview of the observed associations between gut microbial phytoestrogen metabolites and metabolite phenotypes with cardiometabolic risk factors, with focus on the more extensively studied isoflavone metabolites.